Online authentic materials to promote false beginner learners' oral production (2019)
We observed that the development of oral production in our English classes was one of the most difficult features in the communicative process, and on a personal level, we had experienced this problem ourselves. This action research study aimed at inquiring how exposure to conversations done by native and non-native English speakers to a class of false beginners may stimulate speaking. We identified they do not feel comfortable enough to speak according to the obtained results from a semi-structured interview that we applied to false beginner learners in 2017 and 2018. Our 30 participants sample population belongs to two different public schools in Bogota. Some students were interviewed and video recorded as they worked with readings and videos while some others presented a final portfolio with evidence of the process. Preliminary findings indicated that when learners understand the material and become interested in a topic, their oral proficiency increases.